P252 The role of a regional mesothelioma MDT in improving prognostication. (December 2018) - McCracken, DJ; Bedawi, E; Hassan, M; Mercer, R; Asciak, R; Rahman, NM
Abstract : Introduction: Malignant pleural mesothelioma (MPM) is primarily associated with asbestos exposure. Prognosis is poor, with median survival quoted as 6–12 months. Although uncommon, incidence has been steadily increasing and is predicted to peak in 2020. The National Lung Cancer Audit report on MPM (2015), demonstrated significant variation in management and outcomes across the UK and subsequently lead to the production of the British Thoracic Society Guideline for the investigation and management of MPM (2017). This included the recommendation for regional mesothelioma MDTs. We present the findings from the first 15 months of the regional MDT in Oxford and its impact on other recommendations contained within the guidelines. Method: Complete follow up data was collected prospectively from all patients with MPM treated at the Oxford Pleural Unit since 2005. Following the establishment of a mesothelioma MDT in March 2017, 39 patients have been diagnosed and discussed at this meeting. These cases were compared with the 39 preceding cases to assess the impact of the introduction of a specialist MDT. Results: Demographics between both groups were similar. Average age was 77.4 in the MDT group versus 73.8. Sex showed a male predominance in both groups of 82.5%. There was some variation in the distribution of histological subtypes within the groups, however there was an improvement in the number of patients with a clinical diagnosis, no histological subtype or those requiring post-mortem, although sample size was inadequate to achieve significance (table 1). There was no difference in the number of patients being considered for enrolment in clinical trials (33% versus 36%) however there were significant increases in the number of patients who had prognostic scores calculated (54% versus 0%) and those who had formal staging documented (56% versus 21%, p=0.001). Discussion: Mesothelioma MDTs appear to improve documentation and communication of disease stage and prognosis. Further improvement in this area and in the consideration of enrolment in clinical trials may be possible with the introduction of an MDT proforma. Further work is required to assess the impact on diagnostic accuracy which might be best achieved by joint MDT working to obtain required numbers.